Coupling natural and human processes to simulate changes in the water environment in the Dianchi Lake basin, China. Issue 4 (4th July 2017) - Wang, Guilin; Yang, Kun; Yang, Yang; Zhang, Shaohua
Abstract: This study proposes a comprehensive simulation model that couples natural and human processes that have traditionally been simulated and analyzed independently. This model was established to support a risk assessment associated with natural disasters and social emergencies. In this paper, a driving mechanism was refined to reflect changes in the water environment and to understand the natural process of non-point source pollution formation in the Dianchi Lake basin. The land use and land cover model, incorporating the changes from the human activities and the natural process, was constructed to understand how humans affect the land use and land cover in the Dianchi Lake basin. Moreover, this paper studies the effects of land use and land cover changes on the non-point pollution and the urban non-point pollution with the SWAT and SWMM models. The land use and land cover changes, especially the growth and spread of the urban area, are changing the structure of the ecosystem and are degenerating the functions of the ecosystem. Ultimately, this study comprehensively simulated natural and human processes to analyze the effects of the human activities on water environment.